Peningkatan efektivitas pengajaran kimia di masa pandemi dengan media screencast o matic - Sudarsono Sudarsono (Khazanah Pendidikan, 2021)
The purpose of this classroom action research (CAR) is to improve learning outcomes through Screencast O Matic (SoM) learning media. The subjects in the action research were the students in class XI MIPA-1, SMA Negeri 2 Tarakan; there were 35 students (17 male and 18 female students). The class was chosen because the researcher identified that they were the ones adapting quiet hard to the online learnng in pandemic times. The data collection was carried out through observation, action and documentation. This research was conducted in two cycles, each of which with three meetings. Based on the analysis, it is known that the Google Classroom (GC) platform with a screen recording media of SoM has been proven to improve student learning outcomes. This is evidenced by the learning outcomes at each meeting and cycle. The learning outcomes in the first cycle showed an increase of 11.4%, and at the second cycle it had increased to 77.1%. There were 6 students (17.1%) who failed to get the minimum completeness and 2 students  (5.7%) did not attend the last meeting.Thus, it can be concluded that the two learning media, GC with SoM, are proven to improve student learning outcomes. Therefore, it is recommended that teachers provide appropriate learning media, among of which are GC and SoM. The goal is that learning during this pandemic will still present an interesting and easy to follow learning, which should appropriate to  the student needs.